Analisis Pengaruh Return On Asset, Debt To Equity Ratio, Firm Size, Current Ratio, Dan Growth Terhadap Pembayaran Dividen Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2009-2012 - Isa Febrianti; Djuma hir (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study  aims to determine the  effect of  Return On Asset (ROA), Debt Equity Ratio (DER), Firm Size, Current Ratio,  and Growth on Dividend Policy (Studies in Manufacture Companies that listed in BEI over period 2009-2012). Types of  research used in  this  research  is  explanatory research  (research explanation)  that aims  to  explain the  causal relationship  between the  causal variables  through  hypothesis  testing.  The sampling technique  used was  census sampling and obtained a sample of 27 companies. To test the hypothesis proposed in this study used regression analysis. Regression analysis showed that ROA, Current Ratio, and Growth as well as have a significant influence on dividend policy, meanwhile DER and Firm Size have not a  significant influence on dividend policy.  Based on these results, investors can make profitability, liquidity, and growth as reference in predicting the value of dividend policy by companies.Keywords: Return On Asset (ROA), Debt Equity Ratio (DER), Firm Size, Current Ratio, and Growth Dividend Policy